Ciri-ciri usahawan pelajar di Institusi Pengajian Tinggi Awam Malaysia: Program kejuruteraan di UniMAP - Muhammad Faisal, Hamidi; Adi Anuar, Azmin (Universiti Malaysia Perlis (UniMAP), 2011)
The 2nd International Conference on the Roles of Humanities and Social Science in Engineering (ICoHSE 2010) organized by Universiti Malaysia Perlis (UniMAP), 12th - 14th November 2010 at Bayview Beach Resort, Penang, Malaysia.